Foreign Exchange Reserves and Economic Growth of Brazil: A Nonlinear Approach - M. Kashif; N. Singhal; S. Goyal; S. K. Singh (Финансы: теория и практика, 2024)
The research aims to look at the linear and nonlinear causal relationships between Brazil’s accumulated international reserves and economic growth from 1989 Q1 through 2021 Q4. For empirical investigation, this study employed econometric procedures such as the Augmented Dickey Fuller and Zivot-Andrews unit root tests, the linear Granger causality test, Johansen’s cointegration test, the BDS test, and the nonlinear Granger causality test proposed by Hiemstra and Jones. The study concluded that there is a bidirectional linear and non-linear causality between foreign exchange reserve and economic growth. This study fills the gap in the literature by exploring the nonlinear relationship between international reserves and economic growth, while earlier studies primarily explored linear relationships. Foreign trade policymakers can utilize the model developed here to formulate applicable policies about foreign exchange reserves. Based on the findings, the study proposes that Brazil can accrue foreign reserves if surplus assets are invested in alternate sources such as economic infrastructure projects and regional infrastructure development.